Encuadre de la prensa sobre el indulto a Alberto Fujimori en El País, The New York Times y El Comercio - Romero Quinde, Anamaría de los Ángeles (2021)
The present document is based on the coverage made by the digital press of two foreign media, El País and The New York Times, and the local media El Comercio on the humanitarian pardon granted to Alberto Fujimori by then President Pedro Pablo Kuczynski in December 2017. Such event generated significant convulsion in the public opinion, since the news was announced days after the president had been saved from vacancy due to the support of Kenji Fujimori, son of the prisoner, generating suspicions of negotiation between the parties. Based on this case, this research analyzed the approach or framing given to the exposition of this event in journalistic texts in digital format. The methodology used was of a qualitative phenomenological-hermeneutic type. For this purpose, a content analysis of the texts was carried out based on Entman's framing theory and Rodrigo Alsina's newsmaking theory; in addition, interviews with correspondents were included in order to compare the results of the content analysis with the professional experience in this complex field of journalism. The research concludes that, although each newspaper framed the events related to the pardon following different perspectives identifiable in the resolution proposals by their editorial lines, there are differences and coincidences in the production of the news. Which contributes to generate more journalistically finished contents